Study of Effect of Variations in slot dimensions on Fractal Patch antenna Performance - Kumar, Somesh; Monika, Ms. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
An antenna is a device that is made to efficiently radiate and receive radiated Electromagnetic waves. Microstrip antennas are attractive due to their light weight, conformability and low cost. These antennas can be integrated with printed strip-line feed networks and active devices. This is a relatively new area of antenna engineering. For reducing the size of antenna, fractal geometries have been introduced in the design of patch antenna. Fractal antennas also called as space filling curves are very compact, multiband or wideband, and have useful applications in cellular telephone and microwave communications. In our research work, we have used IE3D software for designing the antenna. We study the effect of variations of slot dimensions on antenna performance so as to obtain good results. In this research work, four different fractal patch antennas are designed. The rectangular base geometry is same for the all four antennas but the elliptical slot dimensions differ. In simulation, S parameters of all four antennas are analyzed. From the S parameter displays, comparison of all four antennas is done on the basis of three parameters that are: Lowest frequency, Multiband and S11 values. The simulation results shows that as the elliptical slot dimension decreases on rectangular patch antenna, the performance of fractal patch antenna improves on the basis of three factors that are lowest frequency, multiband and s11 values.